Marketing Malaysia to international tourists / Mohammad Saeed, Bharath M. Josiam and Ismadi Ismail - Saeed, Mohammad; M. Josiam, Bharath; Ismail, Ismadi (Faculty of Business and Management ; UiTM Press, 2000)
The main purpose of this study is to examine the factors that influence the flow of tourists from different countries to Malaysia. We have endeavored to examine the profile of the international tourists and evaluate the economic impact of tourism upon Malaysian economy. Further, the study also involves an examination of the travel patterns and trends in the visitor arrivals, form divergent perspectives. The study involves an analysis of the strengths of Malaysia as an international tourist destination. The objective of the study is to offer appropriate marketing strategies for attracting international tourists to Malaysia.